El senderismo como una alternativa para combatir el sedentarismo en los estudiantes de décimo año paralelo “a” de la unidad educativa “Manuel Ignacio Monteros Valdivieso”, de la ciudad de Loja, periodo 2018-2019 - Jadan Cordero, Cristian Fernando (2020)
The present investigation titled THE TREKKING AS AN ALTERNATIVE TO COMBAT SEDENTARISM IN THE STUDENTS OF PARALLEL YEAR "A" OF THE EDUCATIONAL UNIT "MANUEL IGNACIO MONTEROS VALDIVIESO", OF THE CITY OF LOJA, PERIOD 2018-2019. For the resolution of the problem to be investigated, the following question was raised: Will the practice of hiking be accepted as a recreational alternative to combat sedentary lifestyle with the tenth year students of the “A” parallel of the “Manuel Ignacio Monteros Valdivieso” educational unit? Whose primary objective is framed in; develop trekking as a recreational alternative to combat sedentary life in tenth year parallel children "A" of the educational unit "Manuel Ignacio Monteros" of the city of Loja; scientifically focusing on two variables, the first hiking and the second sedentary in students. The approach of the present investigation is quantitative qualitative, with a type of exploratory-descriptive research, its design is quasi-experimental, during the process the inductive, deductive, analytical, intervalve, continuous, expository, and statistical methods were applied. Techniques such as the survey, the interview, the observation and the tests. The instruments that were used were the questionnaire, the interview guide, the Ruffier Dickson test guide, Burpee test and body mass index test. With the help of the research elements mentioned above, the most significant results could be reached, it was concluded that 100% of the students had improvements in respiratory cardio and muscular endurance, demonstrating that the application of physical activities related to hiking and the practice of it improves the physical condition of the student, finishing that this activity helps to combat sedentary lifestyle. Therefore, it is recommended that hiking be included and adapted in physical culture planning, as an important and multidisciplinary area of knowledge for the development of healthy habits in students and also as an alternative to combat sedentary lifestyle.